Comfort assessment for rehabilitation scaffold in road-railway bridge subjected to train-bridge-scaffold coupling vibration. (15th May 2020) - Zhu, Yan; Chen, Guoqing; Li, Xiaolong; Lu, You; Liu, Jinjun; Xu, Tengfei
Highlights: A strategy to assess comfort of scaffold subjected to moving train is proposed. Dynamic response of scaffold was calculated and tested on-site. Comfort was mainly determined by the vertical dynamic response of the scaffold. Scaffold vibration were affected by structural properties and train speed. Abstract: Rehabilitation scaffolding attached to an operating bridge always vibrates during construction works. Hence, individuals working on the scaffold may feel uncomfortable from exposure to excessive vibration. This paper proposes a strategy to assess the comfort of the scaffold with regard to the train-bridge-scaffold coupling vibration. Thereby, the dynamic response of the scaffold subjected to moving train loads can be calculated using a numerical model of the train-bridge-scaffold coupling vibration. The calculation results were compared with the results obtained by an on-site experiment to validate the numerical model. The vibration acceleration level (VAL) recommended by ISO 2631 was adopted as the comfort index to assess the comfort of the scaffold. A case study considering the Nanjing Yangtze bridge rehabilitation project was carried out to demonstrate the proposed procedure. The assessment results revealed that the comfort index was mainly determined by the vertical dynamic response of the scaffold. The distribution and magnitude of the frequency spectrum of this acceleration response were influenced by the structural stiffness and its spatial distribution, structural mass and its spatial distribution, and train speed. Higher structural stiffness and lower mass resulted in a higher VAL. Additionally, the VAL value increased with the train speed increment.